A Union Indivisible : Secession and the Politics of Slavery in the Border South - Robinson, Michael D. (Book collections on Project MUSE., 2017)
"Michael Robinson challenges the previously held notions on the dichotomy between the free labor North and the slaveholding South. An examination of the Border South states of Delaware, Kentucky, Maryland, and Missouri--all of which ultimately elected to remain in the Union--reveals that this decision was contingent, contentious, and not nearly as straightforward as most scholarship has acknowledged. Robinson provides a more thorough examination of the secession crisis in these four Border South states, shedding light onto the border southerners' varied and often contradictory responses to the crisis of the Union"--